Investigating the Role of Normative Support in Atheists’ Perceptions of Meaning Following Reminders of Death - Soenke, Melissa; Vail, Kenneth E.; Greenberg, Jeff (Frontiers in Psychology, 2022)
According to terror management theory, humans rely on meaningful and permanence-promising cultural worldviews, like religion, to manage mortality concerns. Prior research indicates that, compared to religious individuals, atheists experience lower levels of meaning in life following reminders of death. The present study investigated whether reminders of death would change atheists’ meaning in life after exposure to normative support for atheism. Atheists (N = 222) were either reminded of death or a control topic (dental pain) and exposed to information portraying atheism as either common or rare, and then asked to rate their perceived meaning in life. Results showed that reminders of death reduced meaning in life among atheists who were told that atheism is common. Results were consistent with the view that atheism reflects the rejection of religious faith rather than a meaningful secular terror managing worldview. Discussion considers implications for maintaining healthy existential well-being, identifies limitations, and highlights future research directions.